Legal dimensions and ethical norms of public relations practice in the digital age - Ryabovolyk, Tetiana; Fomichov, Kostiantyn; Lypchanskyi, Volodymyr (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article examines the key legal aspects and ethical standards of PR activity in the context of the digital reality, which is undergoing dynamic transformation under the influence of technological progress, social media, and developments in the field of information security. The legal regulation of public relations is analyzed both within Ukrainian legislation and the international legal framework, particularly in relation to personal data protection, copyright compliance, information dissemination, countering fake news, and the regulation of advertising in the digital environment. Emphasis is placed on the importance of adhering to ethical principles in communication practice, such as truthfulness, transparency, avoidance of manipulation, and respect for audience privacy. Practical recommendations are proposed for conducting lawful PR campaigns, managing information on social media, complying with ethical standards during crisis communication, and minimizing reputational and legal risks. The aim of the article is to identify the current challenges and prospects for legal and ethical regulation of PR activity in the digital age, especially in the context of rapid technological development, the digitalization of communications, and growing public demand for responsible public engagement.

У статті розглянуто ключові юридичні аспекти та етичні стандарти PR-діяльності в умовах цифрової реальності, що динамічно трансформується під впливом технологічного прогресу, соціальних мереж та змін у сфері інформаційної безпеки. Проаналізовано правове регулювання зв’язків з громадськістю як в українському законодавстві, так і в міжнародному правовому полі, зокрема щодо захисту персональних даних, дотримання авторських прав, поширення інформації, протидії фейковим новинам та регулювання реклами в цифровому середовищі. Наголошено на важливості дотримання етичних принципів у комунікаційній практиці, зокрема правдивості, прозорості, недопущення маніпуляцій та поваги до приватності аудиторії. Запропоновано практичні рекомендації щодо правомірного ведення PR-кампаній, обробки інформації в соціальних медіа, дотримання етичних норм під час кризової комунікації, а також мінімізації репутаційних та юридичних ризиків. Метою статті є визначення сучасних викликів і перспектив правового та етичного регулювання PR-діяльності у цифрову епоху, зокрема у контексті стрімкого розвитку технологій, цифровізації комунікацій і зростання суспільного запиту на відповідальну публічну взаємодію.
Юридичні аспекти та етичні стандарти PR-діяльності в умовах цифрової реальності
Keywords: PR activity; legal regulation; communication ethics; digital reality; personal data; fake information; copyright; PR-діяльність; правове регулювання; етика комунікації; цифрова реальність; персональні дані; фейкова інформація; авторське право